THE EFFECT OF MUSCLE TYPE AND LONGER STORAGE TO THE NUTRITION VALUE OF BALI CATTLE - Dewi, Anjelia Martina; Swacita, Ida Bagus Ngurah; Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2016)
The research aimed to find out the influence of muscle type and longer storage of bali beef to the nutrition value consisting of five parameters included water, fat, protein, ash and carbohydrate content originally from the active muscle and passive muscle of bali beef. The results showed that the effect of muscle type was significantly against water, ash, protein and carbohydrate content of bali beef. Moreover, longer storage significantly affect to the water, fat and carbohydrate content. Ash, protein and carbohydrate content of active muscle were higher than the passive muscle, while the water and fat content of active muscle were lower than the passive muscle
Keywords: daging sapi bali; jenis otot; lama penyimpanan; nilai nutrisi; bali beef; muscle type; longer storage; nutrition value